Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Type the correct answer in the box. Use numerals instead of words.

Consider this expression:
[tex]\[ \left|m^2 + n^2\right| \][/tex]

When [tex]\(m = -5\)[/tex] and [tex]\(n = 3\)[/tex], the value of the expression is [tex]\(\boxed{\square}\)[/tex]


Sagot :

To find the value of the expression [tex]\(\left|m^2 + n^2\right|\)[/tex] when [tex]\(m = -5\)[/tex] and [tex]\(n = 3\)[/tex], follow these steps:

1. Square the value of [tex]\(m\)[/tex]:
[tex]\[ m^2 = (-5)^2 = 25 \][/tex]

2. Square the value of [tex]\(n\)[/tex]:
[tex]\[ n^2 = 3^2 = 9 \][/tex]

3. Add the squared values:
[tex]\[ m^2 + n^2 = 25 + 9 = 34 \][/tex]

4. Take the absolute value of the result:
[tex]\[ \left|34\right| = 34 \][/tex]

Therefore, the value of the expression [tex]\(\left|m^2 + n^2\right|\)[/tex] when [tex]\(m = -5\)[/tex] and [tex]\(n = 3\)[/tex] is [tex]\(34\)[/tex].

So, [tex]\(\boxed{34}\)[/tex]